A study on the influence factors of working environment on expatriate staff’s performance in Scope International (M) Sdn Bhd / Alif Salleh - Salleh, Alif (Faculty of Business and Management, 2010)
The central issue of this research is to study on the influence of working environment expatriate staff’s performance in Scope International (M) Sdn. Bhd. which is a wholly owned subsidiary of Standard Chartered Plc, United Kingdom. These means is there any relationship between all the independent variables with the dependent variable. This research basically focuses on the expatriate employees in of Scope International. A framework was developed and tested whereby expatriate staff’s performance is influenced by four elements of working environment which are job sharing, job flexibility, colleague attitude and superior-subordinate relationship. There several problems for Scope International today where most of the expatriate employees are not performing well in their job. So that, the researcher tried to clarify what factors that can contribute to this matter. The research is being narrowed to 40 and randomly chosen respondents as the data sampling in order to identify whether the working environment dimensions has a relationship towards staff’s performance. The findings and analysis were based on the data obtained from the questionnaire responses. The analysis of findings involved the use of Cronbach’s Alpha to measure the reliability of data and descriptive statistics that consist of frequency distributions and measures the central tendencies. Furthermore, the correlation was used to see if there are any significance differences in the means for all variables of interest. Finally the findings of this research are useful to identify the factors that influence working environment towards expatriate staff’s performance in Scope International (M) Sdn. Bhd.